Imidazopyridines as Potent KDM5 Demethylase Inhibitors Promoting Reprogramming Efficiency of Human iPSCs - Dabiri, Yasamin; Gama-Brambila, Rodrigo A.; Taškova, Katerina; Herold, Kristina; Reuter, Stefanie; Adjaye, James; Utikal, Jochen; Mrowka, Ralf; Wang, Jichang; Andrade-Navarro, Miguel A.; Cheng, Xinlai (iScience, 2019)
Pioneering human induced pluripotent stem cell (iPSC)-based pre-clinical studies have raised safety concerns and pinpointed the need for safer and more efficient approaches to generate and maintain patient-specific iPSCs. One approach is searching for compounds that influence pluripotent stem cell reprogramming using functional screens of known drugs. Our high-throughput screening of drug-like hits showed that imidazopyridines-analogs of zolpidem, a sedative-hypnotic drug-are able to improve reprogramming efficiency and facilitate reprogramming of resistant human primary fibroblasts. The lead compound (O4I3) showed a remarkable OCT4 induction, which at least in part is due to the inhibition of H3K4 demethylase (KDM5, also known as JARID1). Experiments demonstrated that KDM5A, but not its homolog KDM5B, serves as a reprogramming barrier by interfering with the enrichment of H3K4Me3 at the OCT4 promoter. Thus our results introduce a new class of KDM5 chemical inhibitors and provide further insight into the pluripotency-related properties of KDM5 family members.